Haptic recognition memory and lateralisation for verbal and nonverbal shapes. Issue 8 (14th September 2021) - Stoycheva, Polina; Kauramäki, Jaakko; Newell, Fiona N.; Tiippana, Kaisa
ABSTRACT: Laterality effects generally refer to an advantage for verbal processing in the left hemisphere and for non-verbal processing in the right hemisphere, and are often demonstrated in memory tasks in vision and audition. In contrast, their role in haptic memory is less understood. In this study, we examined haptic recognition memory and laterality for letters and nonsense shapes. We used both upper and lower case letters, with the latter designed as more complex in shape. Participants performed a recognition memory task with the left and right hand separately. Recognition memory performance (capacity and bias-free d' ) was higher and response times were faster for upper case letters than for lower case letters and nonsense shapes. The right hand performed best for upper case letters when it performed the task after the left hand. This right hand/left hemisphere advantage appeared for upper case letters, but not lower case letters, which also had a lower memory capacity, probably due to their more complex spatial shape. These findings suggest that verbal laterality effects in haptic memory are not very prominent, which may be due to the haptic verbal stimuli being processed mainly as spatial objects without reaching robust verbal coding into memory.